AN EMPIRICAL EXAMINATION OF THE DIVIDEND INFORMATION CONTENTS IN THE BALANCE SHEET: A Signaling Approach* - R. Agus Sartono; Anna Maria Sri Asih (Gadjah Mada International Journal of Business, 2002)
This study examines whether the changes in the financial statements and dividends can together provide a better information transmittal system to deliver missing private information on the firm using Indonesian firms as the sample. In doing so, this study consider three components in evaluating the dividend signaling theory: the expected content favorableness, the sign of dividend change, and the role of dividend signal. Thefinding shows that in Indonesia, the market reactions to the dividend announcements depend on the role of dividend signals, whether it is confirmatory, clarificatory, or unclear. The other finding shows that this market is more concern to the content expected favorableness rather than to the dividend sign.